A self-assembled organic/metal junction for water photo-oxidation - Olaya, Astrid J. (2019)
We report the in situ self-assembly of TTF, TTF ·+ , and BF 4 - or PF 6 - into p-type semiconductors on the surface of Pt microparticles dispersed in water/acetonitrile mixtures. The visible light photoactivation of these self-assemblies leads to water oxidation forming O 2 and H + , with an efficiency of 100% with respect to the initial concentration of TTF ·+ . TTF ·+ is then completely reduced to TTF upon photoreduction with water. The Pt microparticles act as floating microelectrodes whose Fermi level is imposed by the different redox species in solution; here predominantly TTF, TTF ·+ , and HTTF + , which furthermore showed no signs of decomposition in solution.